Design strategies to persuasive learning for promoting sustainable practices in paddy farming - Othman, Zakirah; Muhammad, Amran (Science Publications, 2011)
Problem statement: Public awareness of sustainable agriculture is low, especially in organic paddy practices. As alternative, introducing Information and Communication Technology(ICT) application like electronic learning is an effective way to educate and promote the young generation to appreciate sustainable agriculture. Therefore, the main objective of this study is to discuss a design of a prototype of persuasive learning in virtual paddy as a tool to promote sustainable practices in paddy farming using Malaysia paddy farming practices as a case study. Approach: The real practice in sustainable paddy farming practices has been adapted in design of prototype. A method used for prototype design and development in this study is adapted from the model for design and development created by Alessi and Trollip. After that, a pilot test will be conducted with the help of an expert user. In addition, a lab experiment was conducted in the Computer Laboratory of the Engineering Department, University Putra Malaysia. Respondents from the Biology, Engineering and Agriculture Department student, Faculty of Engineering were selected randomly to answer the usability and awareness questionnaire. Results: Finding of this study shown the way of information and communication technology can facilitate understanding in organic paddy farming practice. The prototype also improves the level of awareness in sustainable agriculture in general. Conclusion/Recommendations: For future study, more research about potential used of learning environment in the sustainable issues can be carried out.